PLATINUM-GROUP-ELEMENT SYSTEMATICS OF PERIDOTITES FROM OPHIOLITE COMPLEXES OF NORTHWEST ANATOLIA, TURKEY: IMPLICATIONS FOR MANTLE METASOMATISM BY MELT PERCOLATION IN A SUPRA-SUBDUCTION ZONE ENVIRONMENT - Aldanmaz E.; Koprubasi N. (My University, 2006)
Platinum-group-element (PGE) studies of peridotites from the supra-subduction zone (SSZ) ophiolites of northwest Anatolia provide evidence for the nature of melt extraction within the upper-most mantle, and interactions between subduction-related magma and oceanic lithosphere. The peridotite samples from the mantle section of the ophiolites are mainly spinel-harzburgites and dunites, accompanied by subordinate amounts of spinel-lherzolite. Whole-rock major-trace element and mineral chemical characteristics indicate that the peridotites originated as the solid residues of varying degrees of partial melting (ε1-5 to ε1-20%), and were subsequently modified by interaction with metasomatizing melts. The samples have non-chondritic, fractionated chondrite-normalized PGE patterns. Melt-depleted (e.g., low Al2O3 and CaO contents) mantle harzburgites and dunites show moderate to strong enrichments in the palladium group relative to the iridium group PGEs (PdN/IrN = 1.81±0.23; N = Cl-chondrite normalized), and in most samples, pronounced Rh and Pd enhancements relative to Pt (RhN/PtN = 2.31 ± 0.66; PdN/PtN = 1.93 ± 0.20). These signatures cannot be reconciled with a simple in situ melt extraction and removal of sulfide phases, but most likely reflect a multi-stage petrogenetic process that selectively enriched the local mantle environment in incompatible and less refractory siderophile elements that are mobilized during continuous melt percolation, while relatively depleting the mantle wedge in Pt, which was not as effectively mobilized by silicate melts (or fluids). The results of quantitative model calculations indicate that t he addition of sulfides that originated from interaction between solid mantle and percolating hydrous basaltic melts may account for the strongly supra-chondritic ratios of both Pd/Ir and Ir/Os, as well as for the formation of abundant chromite deposits within the ophiolite complex. The peridotites show no systematic variation of Ir-group PGE (Ir, Ru, Os; I-PGE) abundances relative to melt depletion indices such as Mg#, Al2O3, CaO, or spinel Cr#, despite their remarkable inter-clement PGE variations. These along with elevated values of strongly incompatible lithophile elements (e.g., Ba, U, and LREE) in the reactive harzburgites and dunites suggest a post-melting metasomatism and melt impregnation in a supra-subduction zone environment. Enrichment in various incompatible elements (Hf, U, Ta, Sr) relative to the expected values for melt-depleted mantle residues and pronounced negative anomalies in fluid-insoluble high-field-strength elements (Ta, Nb, Zr, Hf, Ti) further suggest that both siliceous melts and slab-derived hydrous fluids were involved in mantle metasomatism. Copyright © 2006 by V. H. Winston & Son, Inc. All rights reserved.